An acoustic based risk score in addition to pre-test probability estimation for coronary artery disease improves risk classification in patients with suspected coronary artery disease. (3rd October 2022) - Bjerking, L; Schmidt, S; Wadt Hansen, K; Winther, S; Boettcher, M; Galatius, S; Prescott, E
Abstract: Background: The 2021 American College of Cardiology (ACC)/American Heart Association (AHA) Guideline for Evaluation and Diagnosis of Chest Pain introduced a new pre-test probability (PTP)-table for risk stratification of patients with symptoms suggestive of coronary artery disease (CAD). The CAD-score, an acoustic-based risk score for obstructive CAD, has previously shown good rule out capability in patients with suggested CAD when added to PTP. Purpose: To investigate the potential of the acoustic CAD-score to 1) reclassify patients from intermediate-high to low PTP, and 2) improve risk-stratification in patients with low PTP, when added to the 2021 AHA/ACC PTP. Methods: This is a retrospective study of patients with successfully obtained CAD-score from The Danish study of Non-Invasive testing in Coronary artery Disease 1 (Dan-NICAD 1) of patients without known CAD referred for coronary computed tomography angiography with angina pectoris. Patients with suspected obstructive CAD underwent invasive angiography. CAD-score was obtained with a non-invasive acoustic device analysing heart sounds based on CAD-related turbulence. CAD-score≤20 indicated low probability of CAD. PTP was calculated from sex, age, and angina symptoms according to current AHA/ACC Guidelines. Low likelihood of CAD was defined as PTP≤15%, and intermediate-high likelihood as PTP>15%. Hemodynamic obstructive CAD was defined as visual luminal diameter stenosis >90% on angiography or FFR<0.80%. Results: Among the 1475 included patients (52.3% women, median age 57 years IQR [50–64[), 36.4% were categorized as low likelihood of CAD (PTP≤15%), and 9.8% of patients had obstructive CAD. Compared to patients with PTP≤15%, patients with PTP>15%, were older, more often hypertensive (49.8% vs. 35.5%), had a higher median CAD-score (28 [22–38] vs. 16 [12–22]), and had more obstructive CAD (12.4% vs. 5.2%). CAD-score reclassified 17.6% of patients with intermediate-high likelihood to a low likelihood of CAD and decreased the post-test probability of obstructive CAD from 5.2% to 4.7%. Subgroup analyses showed reclassification was greater in men, patients with PTP ≤25%, age <70 years or no hypertension. In the 432 patients with PTP>15%, age<70 and no hypertension, 35.4% were reclassified to low likelihood, whereas only 2.4% of patients with PTP>15%, age≥70 years or hypertension were ruled out by CAD-score ≤20. In patients with low PTP≤15%, CAD-score≤20 risk-stratified 361 (67.2%) patients to very low and 176 (32.8%) to an intermediate-low likelihood of CAD, but the post-test probabilities of CAD in both subgroups were still below the cut-off of 15 (3.6% vs. 8.5%). Conclusion: Adding an acoustic-based CAD-score to the AHA/ACC PTP could potentially reduce the need for further diagnostic testing by 17.6% in patients with intermediate-high likelihood of CAD and in subgroups a reduction of 35% can be achieved. Use of CAD-score in low-likelihood patients only moderately improves risk classification. Funding Acknowledgement: Type of funding sources: None.